2008
DOI: 10.1159/000171479
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Safety and Performance of the Otologics Fully Implantable Hearing Device: Transducing Sounds via the Round Window Membrane to the Inner Ear

Abstract: Objectives: The safety and performance of the Otologics fully implantable hearing device were assessed in adult patients with mixed conductive and sensorineural hearing loss. Methods: The subcutaneous microphone of this fully implantable device picks up ambient sounds, converts them into an electrical signal, amplifies the signal according to the user’s needs, and sends it to an electromechanical transducer. The transducer tip is customized with a prosthesis in order to be in contact with the round window memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
2
27
2
12
Order By: Relevance
“…Despite the apparent and successful clinical outcomes in a limited number of patients [Colletti et al, 2006;Beltrame et al, 2009;Lefebvre et al, 2009;Martin et al, 2009;Tringali et al, 2009], few experimental data are available regarding the performance expectations of RW stimulation with an AMEI. In the present study, an AMEI was able to successfully drive the RW membrane in all cadaveric temporal bones with a classic facial recess approach.…”
Section: Rationale For Rw Stimulation By Ameimentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the apparent and successful clinical outcomes in a limited number of patients [Colletti et al, 2006;Beltrame et al, 2009;Lefebvre et al, 2009;Martin et al, 2009;Tringali et al, 2009], few experimental data are available regarding the performance expectations of RW stimulation with an AMEI. In the present study, an AMEI was able to successfully drive the RW membrane in all cadaveric temporal bones with a classic facial recess approach.…”
Section: Rationale For Rw Stimulation By Ameimentioning
confidence: 99%
“…The floating mass transducer of the Vibrant Soundbridge from Med-El (Innsbruck, Austria), the Middle Ear Transducer TM from Otologics LLC (Boulder, Colo., USA) and the Esteem 2 (Envoy Medical, St. Paul, Minn., USA) are three commercially available AMEI for the treatment of moderate-to-severe sensorineural hearing loss in adults [Kasic and Fredrickson, 2001;Sterkers et al, 2003;Jenkins et al, 2004Jenkins et al, , 2007Jenkins et al, , 2008; Barbara et al, 2009]. Some of these devices have been applied in conductive or mixed hearing loss therapy [Colletti et al, 2006;Siegert et al, 2007;Venail et al, 2007;Hüttenbrink et al, 2008;Tringali et al, 2008Tringali et al, , 2009Beltrame et al, 2009;Lefebvre et al, 2009;Martin et al, 2009] but none are currently FDA approved for this application. In these cases, the AMEI transducer tips have been modified so that they can be attached to various parts of the ossicular chain, such as the capitulum or footplate of the stapes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are patients with pathologies for which this route of stimulation is not successful or not even possible due to irreparable damage from severe middle ear disease, malformations of the auricle, atresia of the distal auditory meatus, severe otosclerosis, or unsuccessful reconstructions of the ossicular chain (Tringali et al 2008a;Lefebvre et al, 2009). For patients with such pathologies, the traditional route of stimulation to the cochlea via the eardrum, ossicles, and oval window must be bypassed.…”
Section: Implications For Rw Stimulation With Ameps For Hearing Restomentioning
confidence: 99%
“…More recently, some authors have reported successful transfer of mechanical stimuli to the inner ear through the round window (RW) membrane using AMEPs (Colletti et al, 2006;Kiefer et al, 2006;Wollenberg et al, 2007;Lefebvre et al, 2009;Verhaegen et al, 2008) when the traditional route of mechanical stimulation to the cochlea via the ossicles and oval window was not feasible or possible. Despite these successful outcomes with ossicular and RW stimulation on humans, little detailed objective data is available in terms of the physiologic performance of AMEPs, particularly as they pertain to mechanical stimulation of the RW.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, already published studies compared the preoperative with the postoperative air and bone conduction thresholds, as well as with the obtained free-field hearing thresholds, and reported any complications. [2][3][4][5][6][7][8] Hearing benefits, audiological indications, and restrictions were thus evaluated. One already observed limitation is the preoperative hearing threshold, as both MET and Carina can be implanted in patients experiencing moderate or severe hearing loss.…”
Section: Introductionmentioning
confidence: 99%